The Effect of Progressively Unstable Equipment Used in Canine Fitness and Rehabilitation on Standing Postural Control and Muscle Activity - Ramos, Meghan T.; Otto, Cynthia M.; Richards, Jim; Levine, David (Veterinary and Comparative Orthopaedics and Traumatology, 2025)
This study aimed to evaluate the effects of three commonly used postural exercise platforms on the stability of the thoracolumbar and lumbosacral regions and the activity of key muscles (biceps femoris, epaxials, medial gluteal, rectus abdominis, triceps) in dogs.Nine dogs were assessed while standing across two stable platforms (stable stance), two K9FITbones (unstable stance), and on a FitPaws TRAX Peanut (Peanut). To determine spinal stability and muscle activity, angular velocities in three anatomical planes and surface electromyography were measured using Delsys Trigno Sensors.Significant incremental stability challenges were observed across platforms. The thoracolumbar region activity increased in the sagittal (p < 0.001), coronal (p < 0.001), and transverse (p = 0.003) planes with decreasing platform stability. Similarly, the lumbosacral region angular velocity increased in the coronal and transverse plane (p < 0.001), with only the sagittal plane increasing on the Peanut (p < 0.001). Compared with the unstable stance, BF and MG activity was greater during stable stance (p = 0.005) and the Peanut (p = 0.001). RA activity was greater on the Peanut than during stable stance (p = 0.041), suggesting increased abdominal muscle recruitment.Challenging standing postural control with unstable platforms provides substantial and incremental increases in spinal movement and provides insights into muscle activation within progressive rehabilitation exercises.
Keywords: unstable platforms; postural control; surface electromyography; Inertial Measurement Units; canine rehabilitation